2019
DOI: 10.1103/physrevd.100.034008
|View full text |Cite
|
Sign up to set email alerts
|

Masses of ground-state mesons and baryons, including those with heavy quarks

Abstract: Using a confining, symmetry-preserving regularisation of a vector×vector contact interaction, we compute the spectra of ground-state pseudoscalar and vector (fḡ) mesons, scalar and axial-vector (f g) diquarks, and J P = 1/2 + , 3/2 + (f gh) baryons, where f, g, h ∈ {u, d, s, c, b}. The diquark correlations are essentially dynamical and play a key role in formulating and solving the threevalence-quark baryon problems. The baryon spectrum obtained from this largely-algebraic approach reproduces the 22 known expe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 128 publications
(216 reference statements)
8
62
2
Order By: Relevance
“…Although the names for the mesons are the conventional ones, the quark content is also shown explicitly to avoid confusion. An equal spacing rule for pseudoescalar mesons containing one heavy quark is [29,54,55]…”
Section: A Pseudoscalar Mesons and Scalar Diquarksmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the names for the mesons are the conventional ones, the quark content is also shown explicitly to avoid confusion. An equal spacing rule for pseudoescalar mesons containing one heavy quark is [29,54,55]…”
Section: A Pseudoscalar Mesons and Scalar Diquarksmentioning
confidence: 99%
“…The results are reported in Tables V and VI. Equal spacing rule for vector mesons with the same quark content in Eq. (22), [29,54,55] The Eq. (28) is exactly fulfilled for the experimental results and for the HP.…”
Section: B Vector Mesons and Axial-vector Diquarksmentioning
confidence: 99%
See 2 more Smart Citations
“…The masses for the spin quartets Ω ccc (1 4 D J ) are predicted to be in the range of ∼ 5.35−5.42 GeV in present work, which [11] 4769(6) · · · Lattice QCD [12] 4789(6)(21) · · · Lattice QCD [13] 4761(52)(21)(6) · · · Lattice QCD [14] 4734(12)(11)(9) · · · Lattice QCD [9] 4763(6) · · · Lattice QCD [15] · · · 14371 ± 4 ± 11 NRCQM [16] 4965 14834 NRCQM [17] 4798 14396 NRCQM [18] 4763 14371 NRCQM [19] 4801 ± 5 14373 ± 25 QCD Sum Rule [20] 4670 ± 150 13280 ± 100 QCD Sum Rule [21] 4720 ± 120 14300 ± 200 QCD Sum Rule [22] 4990 ± 140 14830 ± 100 Faddeev Equation [23] 4900 13800 Faddeev Equation [24] 4760 14370 Faddeev Equation [25] 4799 14244 Diquark Model [26] 4760 14370 Diquark Model [27] 4800 14370 Variational Method [45] 4799 14396 Variational Method [28] 4760 ± 60 14370 ± 80 Bag model [29] 4777 14276 Bag model [30] 4790 14300 RQM [31] 4803 14569 HCQM [32] 4806 14496 HCQM [33] 4812 ± 85 14566 ± 122 Regge Theory [34] 4834 +82 −81 · · · Regge Theory [35] · · · 14788 ± 80 NRQCD [36] 4900(250) 14700(300) Bathe-Salpeter Equation [37] 4773 · · · RGPEP [38] 4797 14346 is compatible with the predictions from Lattice QCD [9] and NRCQM [17]. From Table VIII, it is found that the mass order for the spin quartets predicted in the literature is very different, in this work we predict a normal order, i.e.,…”
Section: ω CCC (1d) Statesmentioning
confidence: 99%